Clubfoot and Tethered Cord Syndrome: Results of Treatment With the Ponseti Method. Issue 6 (July 2019) - Jackson, Trevor; Jones, Alexander; Miller, Nancy; Georgopoulos, Gaia
Abstract : Background: The Ponseti technique has demonstrated high success rates worldwide for the treatment of idiopathic clubfoot. The purpose of this study was to determine whether clubfoot associated with tethered cord syndrome (TCS) was more resistant to Ponseti treatment than isolated clubfoot. Methods: An IRB-approved retrospective cohort study of subjects undergoing Ponseti treatment of clubfoot between 2002 and 2013 was conducted. Subjects with TCS were matched to subjects with isolated clubfoot (1:2) on the basis of laterality, date of birth, sex, and age at presentation. Subject demographics, number of casts placed (pretenotomy and posttenotomy), and recurrence data were collected. Generalized logistic regression and linear mixed model regression analyses were used to compare recurrence within 2 years of the initiation of casting and the log number of casts needed to achieve an acceptable correction, respectively. Results: Data from 24 subjects (16 isolated clubfeet, 8 with TCS) with clubfoot (12 bilateral, 12 unilateral) were analyzed. The isolated clubfoot group was the same age at presentation on average (21.9±4.7 d) as the TCS group (28.3±9.6 d) ( P =0.55). The number of casts required to achieve an acceptable correction was 54% higher (95% CI, 7.8%-120.3%; P =0.0217) in the TCS group compared with the isolated clubfoot group. The cumulative crude incidence of deformity recurrence within the first 2 years after casting initiation was 8% in the isolated clubfoot group compared with 42% in the TCS group. The odds of deformity recurrence in the TCS group were 5.6 (95% CI, 0.7-45.2; P =0.1054) times the odds of deformity recurrence in the isolated clubfoot group. Furthermore, the incidence of deformity recurrence was higher among subjects who had a tethered cord release posttenotomy (56%, 5/9) as compared with pretenotomy (0%, 0/3). Conclusion: Clubfoot associated with TCS required more casts to achieve an acceptable correction. Subjects with tethered cord were also at an increased risk of deformity recurrence compared with subjects with isolated clubfoot. Level of Evidence: Level II—retrospective prognostic study.